A facile one‐step synthesis of bio‐inspired porous graphitic carbon sheets for improved lithium‐sulfur battery performance. (29th October 2021) - Harimohan, Erabhoina; Nanaji, Katchala; Rao, Boyapati Venkat Appa; Rao, Tata Narasinga
Summary: The development of cost‐effective carbon materials with tunable porosity for energy storage applications is challenging. In this study, a facile one‐step in situ chemical activation process was adopted to synthesize porous graphitic carbon sheets (GCSs) from a tissue paper. The resulting GCS exhibits high specific surface area, large pore volume, and a highly graphitized carbon structure with graphene‐like morphology. Sulfur‐infused GCSs with optimum sulfur loading along with GCS‐coated separator deliver a high initial discharge capacity of 1643 mAh g −1 at 0.1C rate. Moreover, when the electrode is tested at a high current rate of 1C, the cell delivered excellent cyclic stability of 652 mAh g −1 over 200 cycles. The improved electrochemical performance attributes to the unique properties of GCS, which functions as an efficient host matrix as well as an interlayer by constraining the dissolved polysulfides in addition to the enhancement in ionic and electronic conductivities. Abstract : Graphitic Carbon Sheets are prepared by a facile one‐step in‐situ activation process from a tissue paper and utilized as a matrix for sulfur cathode and also coated on separator to prevent the polysulfide dissolution for Li‐S battery application.